Equality Between Muslims and Christians in Tolerant Inter-Religious Dialogue in Bekasi - Acep Aripudin; Luthfi Riza Firdaus (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2022)
Equality Between Muslims and Christians in Tolerant Inter-Religious Dialogue in Bekasi Acep Aripudin Pascasarjana UIN Sunan Gunung Djati Bandung Luthfi Riza Firdaus Pascasarjana UIN Sunan Gunung Djati Bandung Abstract Indonesian society is known as a plural, plural and heterogeneous society. This heterogeneity is manifested by the many ethnicities, cultures, religions, and customs. This pluralism places Indonesia as a conflict-prone society as well as a portrait of harmony between people of different religions. This article constructs the effectiveness of equality in dialogue between Islam and Christianity in realizing harmonious and equal relations between people of different religions through tolerant dialogue between Islam and Christianity. The practice of equality in this dialogue can be seen in the process of interaction and communication between Muslims and Christians in Kampung Sawah Bekasi in realizing a harmonious life despite different beliefs. Tolerant dialogue is carried out at moments of hospitality and religious events, such as sharing at Eid and Christmas events. Keywords: Equality, Islam, Christianity, Tolerant Dialogue Abstrak Masyarakat Indonesia dikenal sebagai masyarakat yang plural, majemuk, dan heterogen. Heterogenitas tersebut berwujud dengan banyaknya etnis, budaya, agama, dan adat istiadat. Kemajemukan tersebut menempatkan Indonesia sebagai masyarakat yang rentan konflik sekaligus potret kehidupan harmoni antarumat berbeda agama. Artikel ini mengontruksi efektivitas kesetaraan dalam dialog di antara Islam dan Kristen dalam mewujudkan relasi antarumat berbeda agama yang harmoni, dan setara melalui dialog yang toleran antara Islam dan Kristen. Praktik equality dalam dialog tersebut nampak pada proses interaksi dan komunikasi antara umat Islam dan Kristen di Kampung Sawah Bekasi dalam mewujudkan kehidupan harmonis meskipun berbeda keyakinan. Dialog toleran dilakukan pada momen-momen silaturahmi dan event keagamaan, seperti saling berbagi pada acara Lebaran dan Natal. Kata Kunci: Equality, Islam, Kristen, Dialog Toleran